Does having more power make people more materialistic? The role of personal sense of power for gift preferences - Liang, Shichang; Han, Xiaoyan; Yuan, Xueying; Liang, Meiting; Zhang, Yiwei; Liu, Zhen; Xie, Pin (Frontiers in Psychology, 2023)
：Gift-giving is a common practice in daily life, and studies indicate that experiential gifts have hedonic and interpersonal benefits. Recipients find them more satisfying than material gifts. However, experiential gifts may not always be as well-received as expected, and material gifts are often appreciated for their lasting qualities. Thus, it is essential to understand the scenarios in which gift recipients prefer either material or experiential gifts. Current research has primarily focused on extrinsic factors such as income and social distance, with less attention given to intrinsic factors such as the personal sense of power in interpersonal interactions. In light of the above, drawing on the Agentic-communal Model of Power, we examined the impact of a personal sense of power on gift preferences in three studies, showed that gift preferences were found to be contingent upon a personal sense of power. Specifically, individuals with a high personal sense of power preferred material gifts to experiential gifts, while individuals with a low personal sense of power preferred experiential gifts to material gifts. And information processing fluency mediates the relationship between a personal sense of power and gift preference. These results add to the literature on gift preferences as well as personal sense of power and have important managerial implications.